Escaping from allegories:cat’s eye and King Lear - Caroline Cakebread (Ilha do Desterro)
In her 1972 study of Canadian literature, aptly titled Survival, Margaret Atwood uses the symbol of the mirror to describe the difficulty faced by Canadian writers and artists, struggling to assert their voices in a country trying to define itself against a colonial past.Here, she sees Canada as squeezed between the overwhelming, colonizing powers of Great Britain on one side, and The United States on the other. In her view, a piece of art becomes a mirror. As she writes: If a country or a culture lacks such mirrors it has no way of knowing what it looks like; it must travel blind. If, as has long been the case in [Canada], the viewer is given a mirror that reflects not him but someone else, and told at the same time that the reflection he sees is himself, he will get a very distorted idea of what he is really like. He will also get a distorted idea of what other people are like: it’s hard to find out who anyone else is until you have found out who you are. (15-16) With its roots in Lacanian psychoanalysis, the mirror Atwood describes provides an unreliable reflection for burgeoning artists inCanada: up against the powerful countries that surround them she sees a major identity crisis. Sixteen years later, her 1988 novel, Cat’s Eye, treads similar ground, tracking as it does the passage of its protagonist—painter, Elaine Risley—through childhood in mid-century Canada to her development as an established artist in the 1980s. It is into this narrative that Atwood places extensive references to Shakespeare’s tragedy, King Lear—a play that deals with the notion of identity. Here, Lear’s question, “Who is it that can tell me who I am?” becomes Elaine’s, as she ventures back to Toronto to attend a retrospective of her work at a women’s art gallery named “Sub-Versions.”